(untitled) (Revista Latino-Americana de Enfermagem, 2015)
Objective: to analyze the complications related to peritonitis and catheter exit-site infections, in patients on peritoneal dialysis at home.Method: quantitative and cross-sectional study, carried out with 90 patients on peritoneal dialysis at home, in a municipality in the Northeast region of Brazil. For data collection, it was used two structured scripts and consultation on medical records. Descriptive analysis and comparison tests among independent groups were used, considering p